Enteric fever masquerading as Crohn's disease in a child with abdominal tuberculosis. Issue 2 (9th February 2023) - Sahoo, Bishnupriya; Kumar, Karunesh; Malhotra, Smita; Sibal, Anupam
Abstract : In tropical countries, like India, various types of infectious diseases like tuberculosis, enteric fever, malaria and dengue are prevalent. Disease trend over time has been gradually shifting from infective to inflammatory frame because of increasing awareness regarding hygiene and increasing immunisation coverage. This case report describes an adolescent boy having a long history of abdominal pain, bleeding per rectum and documented weight loss, presented with an acute episode of fever. But the coexisting infections and/or inflammatory conditions presented challenges to the treating physician in diagnosis and management despite of good clinical experience. In this case, a chronic gastrointestinal infection caused by Mycobacterium tuberculosis with a superadded Salmonella typhi infection was masquerading as inflammatory bowel disease (Crohn's disease). Utmost caution should be exercised to reach the correct diagnosis and take the necessary steps to manage this type of situation in tropical countries like India.